Management of acute open tendo-achilles injuries in Indian lavatory pans - S Chatterjee Sasanka; Sarkar Arindam; Misra Ashutosh (Indian Journal of Plastic Surgery)
Injuries to the Tendo-achilles are common but rarely do they present directly to plastic surgeons. Eighteen patients with acute tendo-achilles injury due to fall in the lndian type of lavatory pan came directly to the emergency department of Institute of Post Graduate Medical Education and Research, Kolkata and subsequently were treated in the Department of Plastic Surgery. Direct repair with prolene or stainless steel (SS) wires with or without flap cover were performed for management. Exercises were started 1 month later with gradual increase in activity. Complications were minor and temporary in nature. Long term results in the form of performing previous activities were excellent.